Path and Trajectory Planning of Unmanned Ground Vehicles with Vehicle Dynamic Characters - Il Hun Ryu; Thae Song Pak; Jong Chol Kil; Chun Nam Kim (International Journal of Robotics and Automation in Mechanics, 2024)
Given partial knowledge about its environment (obstacle, road…) and goal position, optimal path and trajectory planning is a key problem for the control of unmanned vehicles. In path planning problem, it is very important to consider the dynamic limits of the vehicle with optimization function. The path planning was implemented by applying optimization methods based on the given obstacle information(virtual or measured by sensor system) and numerical map without considering vehicle dynamic characters. Then, considering the dynamic characters, trajectory planning was carried out to generate the trajectory that the vehicle can actually travels. This method has certain errors and some shortcomings in finding the optimal solution because the path planning and trajectory planning are carried out independently of each other. One way to solve this problem is to combine these two subjects and to find a global optimal solution. Thus, during the course of the path planning, the constraints necessary for the trajectory planning are considered and the optimization function is chosen accordingly. This paper describes a hybridized algorithm of path planning and trajectory planning, in which optimization function is determined for shortest-length, shortest-time, minimum speed variation path, and the vehicle dynamics characters are considered reasonably. Longitudinal and Lateral Vehicle dynamic models are applied and solutions are solved using genetic algorithm. Also, it is analyzed the effect of weight coefficients to the path planning and trajectory planning. This paper gives practical and useful helps to the engineers and researchers who are trying for the autonomous navigation of the unmanned ground vehicle
Keywords: Unmanned ground vehicle; path planning; trajectory planning; vehicle dynamic model